A comparative study on mechanical performance of traditional and magnetically assisted resistance spot welds of A7N01 aluminum alloy. (June 2021) - Qi, Lin; Zhang, Qingxin; Ma, Yunwu; Xu, Ye; Han, Xiaohui; Li, Yongbing
Graphical abstract: Highlights: A novel type of single-sided magnetically assisted apparatus was developed for 7xxx series aluminum alloy RSW process. Influencing mechanism of induced and external magnetic fields on weld macro and microstructure were revealed. Improving mechanism of external magnetic field on weld performance in lap-shear, cross-tension, and fatigue tests were studied. Abstract: In this paper, an external magnetic field was introduced to resistance spot welding (RSW) to improve the weldability of A7N01 aluminum alloy. Comparative studies of the macro- and micro-structures, microhardness, and the static and dynamic mechanical properties between welds produced by traditional RSW and magnetically assisted RSW (MA-RSW) were completed. The results show that the external magnetic field could enable larger nugget diameter, the softened columnar grain zone (CGZ-I), the hardened columnar grain zone (CGZ-II) and the finer equiaxed grain zone (EGZ). As a result, compared to traditional RSW joints, the MA-RSW joints exhibited better strength, improved toughness, and greater energy absorption capacity. This resulted in a transition of the failure mode from an interfacial fracture (IF) to a partial thickness fracture (PTF) in lap-shear tests and a BP fracture in cross-tension tests, respectively. In fatigue tests, the larger nugget diameter, hardened CGZ-II and finer EGZ in the MA-RSW welds can inhibit cracks from propagating from EGZ, but from the softened CGZ to the base metal. This change of fracture mode greatly improved the fatigue life of MA-RSW welds under both high and low load conditions.